1971
DOI: 10.1177/074171367102200102
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the Adult Learner in Program Planning

Abstract: This study investigated the influence of participation in program planning on achievement and attitude. Two experimental groups participated in planning their educational programs. Two control groups completed courses identical to the corresponding experi mental groups, but they did not help plan them. A two hundred item achievement measure and a twelve concept semantic differ ential attitude measure were administered to both groups. The results of a t-test analysis of group mean scores permitted two conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The study also challenges adult educators to test the hypothesis advanced by Knowles (8,9,10,11,12,13), London (14), Bergevin (1), and others that instructor involvement of students in program design and operation is the most effective way of facilitating learning in adults. Since 1965, when Verner and Kulik (17) stated that program planning was &dquo;an uncharted field in which research of any sort would be fruitful,&dquo; very few studies -such as those by Welden (18), McLoughlin (15), and Cole and Glass (2) -have examined the relationship of student involvement in the design and operation of an educational program with such variables as student learning and student attitudes. Further research on the student-perceived teaching behavior of postsecondary educators, which includes student involvement behaviors, should help to clarify these relationships.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The study also challenges adult educators to test the hypothesis advanced by Knowles (8,9,10,11,12,13), London (14), Bergevin (1), and others that instructor involvement of students in program design and operation is the most effective way of facilitating learning in adults. Since 1965, when Verner and Kulik (17) stated that program planning was &dquo;an uncharted field in which research of any sort would be fruitful,&dquo; very few studies -such as those by Welden (18), McLoughlin (15), and Cole and Glass (2) -have examined the relationship of student involvement in the design and operation of an educational program with such variables as student learning and student attitudes. Further research on the student-perceived teaching behavior of postsecondary educators, which includes student involvement behaviors, should help to clarify these relationships.…”
Section: Resultsmentioning
confidence: 98%
“…The first item (15) states that the instructor does not recognize individual differences among students, and the second item (20) states that the instructor has seldom known the average students as individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing a participative experimental group and a nonparticipative control group, McLoughlin (15) noted that sharing the decisions of course content and design produced no measurable increase in achievement. Although his study failed to support the relationship between participation and achievement, McLoughlin cautioned educators against drawing hasty conclusions in this area:…”
Section: Review Of the Literaturementioning
confidence: 98%
“…Few studies (8) (12) (15) (24) have treated participation as an independent variable and focused on student participation in setting course objectives and designing the learning experience. Welden (24) investigated program-planning effectiveness in university residential centers through comparing programs planned with participant representation and programs planned without participant representation.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In a study at the Office of Civil Defence Staff College, McLoughlin (1971) found that adults who participated in program planning had more positive attitudes about their learning experience than those who did not participate in planning. This study did not show a relationship between student planning and achievement, as measured by a multiple-choice achievement test.…”
mentioning
confidence: 99%